2007
DOI: 10.1142/s0192415x07004862
|View full text |Cite
|
Sign up to set email alerts
|

Sho-Saiko-To (Xiao-Chai-Hu-Tang) and Crude Saikosaponins Inhibit Hepatitis B Virus in a Stable HBV-Producing Cell Line

Abstract: To search for an effective antiviral agent, this study tested the hypothesis that sho-saiko-to (Xiao-Chai-Hu-Tang) and crude saikosaponins possess the activity directly against HBV and could affect the expressions of viral antigens, HBeAg and HBsAg, in HepG(2) 2.2.15 cell model. The viral amount and viral antigens in the suspension were estimated by quantitative real time PCR and enzyme-linked immunosorbent assay (ELISA), respectively. The results showed that sho-saiko-to could inhibit the production of HBV (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 22 publications
0
25
0
1
Order By: Relevance
“…It is usually difficult to separate the inflammatory process from the immune response; drugs with immunomodulatory [75,76] Alcoholic extract (-) Helicobacter pylori activity [77] Saikosaponin C (-) Hepatitis B replication [75] B. falcatum Acidic polysaccharide fraction (-) Gastric lesions [78] Saikosaponin mixture (-) Acute and chronic inflammation [79] Bupleuran 2IIc (-) Gastric lesions [80][81][82] (+) Gastric mucosa regeneration Saikosaponin A (+) B cells [83][84][85][86][87][88] (-) T cells (-) PGE2 (-) sGOT and sGPT levels (-) Lipid peroxidation (-) Asthmatic bronchoconstriction Saikosaponin D (+) Macrophage phagocytosis [75,[84][85][86][87][92][93][94] (-) T cells (+) Acid phosphatase (+) IL-2/IL-4 production (-) NF-kB (-) IL-6, TNF-a, IFN-g (+) PGE2 production (-) sGOT, sGPT and TGF-b1 levels (-) Lipid peroxidation Cytotoxic against HepG2 cell line (-) Measles and herpes viruses Saikosaponin B1…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…It is usually difficult to separate the inflammatory process from the immune response; drugs with immunomodulatory [75,76] Alcoholic extract (-) Helicobacter pylori activity [77] Saikosaponin C (-) Hepatitis B replication [75] B. falcatum Acidic polysaccharide fraction (-) Gastric lesions [78] Saikosaponin mixture (-) Acute and chronic inflammation [79] Bupleuran 2IIc (-) Gastric lesions [80][81][82] (+) Gastric mucosa regeneration Saikosaponin A (+) B cells [83][84][85][86][87][88] (-) T cells (-) PGE2 (-) sGOT and sGPT levels (-) Lipid peroxidation (-) Asthmatic bronchoconstriction Saikosaponin D (+) Macrophage phagocytosis [75,[84][85][86][87][92][93][94] (-) T cells (+) Acid phosphatase (+) IL-2/IL-4 production (-) NF-kB (-) IL-6, TNF-a, IFN-g (+) PGE2 production (-) sGOT, sGPT and TGF-b1 levels (-) Lipid peroxidation Cytotoxic against HepG2 cell line (-) Measles and herpes viruses Saikosaponin B1…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…[66] Chang and coworkers showed that a crude saikosaponin mixture obtained from B. chinense inhibited DNA replication of hepatitis B virus (HBV) and significantly reduced the HBV antigen level in transfected HepG2 cells. [75,76] The main active saikosaponin responsible for the activity was saikosaponin C; it showed a potent inhibition of both HBeAg secretion (IC50 of 11 mg/ml) and HBV-DNA expression (IC50 of 13.1 mg/ml). This activity was much higher than that obtained by the well-known antiviral drug lamivudine, which is the most widely accepted drug for treatment of chronic HBV.…”
Section: Antiviral Activitymentioning
confidence: 99%
“…It is composed of seven herbs including Radix bupleuri, Radix scutellariae, Radix glycyrrhizae, Radix ginseng, Rhizoma pinelliae, Rhizoma zingiberis recens, and Fructus jujubae. Xiaochaihu Tang is widely used to treat chronic hepatitis [1][2][3], it also has cytoprotective effects in experimental liver injuries [4,5], preventive and therapeutic effects in experimental hepatic fibrosis via inhibition of hepatic stellate cells and lipid peroxidation in hepatocytes [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, increasing researches have been carried out on B. chinense, and the results show that the saikosaponin, flavonoid, essential oil and fatty acid possessed several proven pharmacologic activities, including hepato-protective, mild sedative, antipyretic, analgesic, anti-tussive, immunomodulatory effect, anti-fibrotic effect, inhibit growth of liver cancer cells and promotion of liver regeneration (Chang et al, 2007;Sun, 2006;Yin, Pan, Chen, & Hua, 2008;Zhang, Zhou, & Wang, 2007). Therefore, in Japan, Korea and China, it has been widely prescribed to outpatients for treating chronic liver diseases.…”
Section: Introductionmentioning
confidence: 99%